Mô hình mật độ vỏ trái đất lãnh thổ Việt Nam - Triều, Cao Đình (Journal of Computer Science and Cybernetics, 2016)
Gravity inverse problems of 2D and 3D have been used by the author for studying the density model of the Earth crust and adjoined to upper Mantle boundary in the territory of Vietnam.